Surfactant-Mediated Airway and Acinar Interactions in a Multi-Scale Model of a Healthy Lung - Ma, Haoran; Fujioka, Hideki; Halpern, David; Gaver, Donald P. (Frontiers in Physiology, 2020)
We present a computational multi-scale model of a lobe of an adult human lung that combines dynamic surfactant physicochemical interactions and parenchymal tethering between approximately 16 generations of airways and subtended acini. This model simulates the healthy lung by modeling nonlinear stress distributions from airway/alveolar interdependency. In concert with multi-component surfactant transport processes, this serves to stabilize highly compliant interacting structures. This computational model, with ~10k degrees of freedom, demonstrates physiological processes in the normal lung such as multi-layer surfactant transport and pressure-volume hysteresis behavior. Furthermore, this model predicts non-equilibrium stress distributions due to compliance mismatches between airway and alveolar structures. This computational model provides a baseline for the exploration of multi-scale interactions of pathological conditions that can further our understanding of disease processes and guide the development of protective ventilation strategies for the treatment of acute respiratory distress syndrome (ARDS) that can result from the novel coronavirus 2019-nCoV and vaping-related eVALI.